2013
DOI: 10.1177/1090198113505852
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Parent Support for Condom Education and Availability

Abstract: Expanding condom-related knowledge and skills and reducing barriers to condom use have the potential to help reduce pregnancies and sexually transmitted infections among youth. These goals are sometimes addressed through condom education and availability (CEA) programs as part of sexuality education in school. Parents are a key constituency in efforts to implement such programs. A representative statewide sample of households with children (N = 1,093) in California was employed to examine parent support for CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…Overall, the community was supportive of testing for STIs/HIV, treatment for STIs/HIV, and provision of condoms to students in both MS and HS. These findings are consistent with the sparse literature showing support for distribution of condoms and contraceptives by the schools/SBHCs . Fewer participants supported offering these 3 services in MS than in HS.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Overall, the community was supportive of testing for STIs/HIV, treatment for STIs/HIV, and provision of condoms to students in both MS and HS. These findings are consistent with the sparse literature showing support for distribution of condoms and contraceptives by the schools/SBHCs . Fewer participants supported offering these 3 services in MS than in HS.…”
Section: Discussionsupporting
confidence: 88%
“…Although recent studies on support for sexual health services are lacking, there are some studies supporting these findings. Several studies have found that those who identify as politically liberal are more likely to support condom education and access in schools than those who identify as politically conservative, while another found greater support for comprehensive sexuality education among those who identify as politically liberal . In the current study, those in the middle age range (40‐59) were less likely to support STI/HIV testing, STI/HIV treatment, and condom distribution in MS.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations